1998
DOI: 10.1146/annurev.earth.26.1.189
|View full text |Cite
|
Sign up to set email alerts
|

Noble Gases in the Earth's Mantle

Abstract: Noble gas isotopic ratios in mantle-derived samples require variability in the timeintegrated ratio of volatile to lithophile elements in the Earth. Documentation of mantle 3 He/ 4 He variability is becoming increasingly complete, but for the heavier noble gases, the picture is still partly clouded by the effects of atmospheric contamination of mantle samples. Nevertheless, clear variations in mantle Ne, Ar, and Xe isotopic ratios exist, are apparently correlated with 3 He/ 4 He, and may be the product of vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(108 citation statements)
references
References 98 publications
3
103
1
1
Order By: Relevance
“…We measured high 3 He/ 4 He ratios for high temperature fumaroles (>800°C), slightly above 8 Ra which coincides with the widely accepted MORB value of 8 ± 1 Ra (Hilton et al, 1993a;Ozima, 1994;Farley and Neroda, 1998 and references included). Compared to other Japanese volcanic systems, they correspond to the upper range of the values measured for this subduction-related volcanic zone (Nagao et al, 1981;Sano and Wakita, 1985;Marty et al, 1989).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We measured high 3 He/ 4 He ratios for high temperature fumaroles (>800°C), slightly above 8 Ra which coincides with the widely accepted MORB value of 8 ± 1 Ra (Hilton et al, 1993a;Ozima, 1994;Farley and Neroda, 1998 and references included). Compared to other Japanese volcanic systems, they correspond to the upper range of the values measured for this subduction-related volcanic zone (Nagao et al, 1981;Sano and Wakita, 1985;Marty et al, 1989).…”
Section: Resultssupporting
confidence: 86%
“…In this aim, helium has interesting properties: a gaseous state, inertness, and above all, its isotopes show contrasting ratios in the continental crust (<0.1 Ra, Ra being the atmospheric ratio) and in the upper (about 8 Ra) and lower (>30 Ra) mantle (Ozima, 1994;Farley and Neroda, 1998). Therefore it has proven to be a powerful tracer of the origin and possible crustal dilution of mantle-derived fluids (i.e., Hilton et al, 1993b;Van Soest et al, 1998) and of short-term variations induced by active volcanism (i.e., Sano et al, 1997).…”
Section: *Corresponding Authormentioning
confidence: 99%
“…Measurements of Ar and Kr isotopes in ice cores can lead to estimation of firn thickness and temperature (Craig and Wiens, 1996;Severinghaus et al, 2001Severinghaus et al, , 2003. Noble gases in mantle-derived rocks have been used to infer properties of the early history of the earth (Honda et al, 1991;Hiyagon et al, 1992;Farley and Neroda, 1998). Noble gas isotopes produced by cosmic rays yield surface exposure ages for terrestrial rocks (Lal, 1991;Bierman, 1994;Schafer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Such analyses have shown that Mid Oceanic Ridge Basalts (MORB) have uniform 3 He/ 4 He ratios that are higher than the air value (Ra) by about a factor of 8. In contrast, Oceanic Island Basalts (OIB) have variable and much higher value than the air value by a factor of about 12-30 (e.g., Farley and Neroda, 1998). Volcanic gases of mantle origin have ratios similar to those in MORB.…”
Section: Introductionmentioning
confidence: 99%